Bus Services in Dhaka City - Users’ Experiences and Opinions (Journal of Bangladesh Institute of Planners, 2012)
Buses are the only available organized mass public transport system in Dhaka. However, the city is planning to have bus rapid transit (BRT) systems and metro systems to cater the increasing demand for public transport. The buses in Dhaka mostly remain over-crowded, which is often not accessible for the elderly or disabled people as well as for the women. Moreover, the frequency of bus service (headway) is not good. The paper reports the existing service and the users’ opinion about the service level of public bus operating within the city. For this purpose, 5 different bus routes had been chosen and a total of 175 passengers of bus (30 from each route) had interviewed with a pre determined structured questionnaire to know their experience/satisfaction and opinion about the existing service as well as their expectations. Surprisingly, it was found that most of the respondents are satisfied with the cost of ticket but very unsatisfied with the waiting time as they have to wait for the bus sometimes about an hour.Journal of Bangladesh Institute of Planners, Vol. 5, Dec 2012, pp. 93-105